2000
DOI: 10.1074/jbc.m909782199
|View full text |Cite
|
Sign up to set email alerts
|

Zinedin, SG2NA, and Striatin Are Calmodulin-binding, WD Repeat Proteins Principally Expressed in the Brain

Abstract: Striatin is an intracellular protein characterized by four protein-protein interaction domains, a caveolinbinding motif, a coiled-coil structure, a calmodulinbinding domain, and a WD repeat domain, suggesting that it is a signaling or a scaffold protein. Down-regulation of striatin, which is expressed in a few subsets of neurons, impairs the growth of dendrites as well as rat locomotor activity (Bartoli, M., Ternaux, J. P., Forni, C., Portalier, P., Salin, P., Amalric, M., and Monneron, A. (1999) J. Neurobiol.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
174
0
6

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 113 publications
(184 citation statements)
references
References 27 publications
4
174
0
6
Order By: Relevance
“…Phocein was wholly solubilized from a 100,000 ϫ g pellet using nonionic detergents such as Lubrol-PX or zwitterionic detergents such as 3-([3-cholamidopropyl]dimethylammonio)-2-hydroxy-1-propanesulfonate. Striatin and the other proteins of its family, zinedin and SG2NA, behave in the same way (Castets et al, 1996(Castets et al, , 2000Bartoli et al, 1998).…”
Section: Brain Phocein Is Both Cytosolic and Associated With Membranesmentioning
confidence: 86%
See 4 more Smart Citations
“…Phocein was wholly solubilized from a 100,000 ϫ g pellet using nonionic detergents such as Lubrol-PX or zwitterionic detergents such as 3-([3-cholamidopropyl]dimethylammonio)-2-hydroxy-1-propanesulfonate. Striatin and the other proteins of its family, zinedin and SG2NA, behave in the same way (Castets et al, 1996(Castets et al, , 2000Bartoli et al, 1998).…”
Section: Brain Phocein Is Both Cytosolic and Associated With Membranesmentioning
confidence: 86%
“…Validation of the interaction between phocein and striatin by in vitro experiments was straightforward. The respective interactions of phocein with SG2NA and zinedin, which belong to the striatin family (Castets et al, 2000), were also demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations